(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This study investigates the process formation framework for implementing a Quality Management System (QMS) in water purification and bottling enterprises in accordance with ISO 9001:2015, combined with experimental design methodology. The key innovation of the research is the development of a 2^3 full factorial experimental matrix (8 runs) based on three control factors: filter material type (A), inlet water pH level (B), and initial water contamination level (C). Using the PDCA cycle, Key Performance Indicators (KPI) were established, and an analytical methodology based on Analysis of Variance (ANOVA) is presented to evaluate factor effects. The study provides a practical optimization tool for water treatment enterprises operating in Uzbekistan.